Short selling, the supply side: are lenders price makers ? - Casula, Daniel de Sales (2019)
It is widely accepted in the literature that high lending fees predict negative returns because high fees capture the negative information from short sellers, on the demand side. Traditionally, the supply side is seen as passive, in which stock lenders act as price takers. Recent studies, however, have shown that this passivity of lenders no longer perpetuates. Faced with this discussion, the present study analyze the Brazilian stock loan market and disentangles the shorting demand and shorting supply curve shifts in order to understand the driving mechanism linking the supply side and stock returns. We also link the shorting supply curve with new announcements and verify how lenders react to a new information in the market. Our results indicate that lenders decrease the loan supply when they predict negative future returns and that they use new information to change supply conditions, indicating that lenders are not price takers